2015
DOI: 10.1111/ijcs.12202
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and preference for functional foods: the perspective of older Italian consumers

Abstract: The literature has identified several factors that specifically influence how older consumers view and consume functional foods (FFs), including the perceived need for the product and perceived health benefit. Health claims (HCs), symbols and logos on FF labels can thus play a central role in enhancing product attractiveness and perception of health benefits. Nevertheless, few studies have examined how elderly consumers perceive non-verbal communication (such as symbols) associated with health-related informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 54 publications
5
29
0
1
Order By: Relevance
“…Table 1 clearly shows that numerous factors influence consumers when assessing the healthiness of a product. In our literature analysis, we categorized these factors as follows: Communicated information [ 26 , 27 , 34 , 35 , 37 , 47 , 60 , 62 , 65 , 73 , 74 , 77 ]; The shape and colour of the product packaging [ 23 , 25 , 28 , 32 , 33 , 43 , 61 , 66 , 70 , 71 ]; The ingredients of the product [ 24 , 29 , 39 , 40 , 49 , 57 , 64 , 76 ]; Product category [ 54 , 61 , 69 , 70 , 75 , 78 ]; Organic origin of the product [ 5 , 31 , 42 , 45 , 46 , 48 , 51 , 55 , 68 ]...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 clearly shows that numerous factors influence consumers when assessing the healthiness of a product. In our literature analysis, we categorized these factors as follows: Communicated information [ 26 , 27 , 34 , 35 , 37 , 47 , 60 , 62 , 65 , 73 , 74 , 77 ]; The shape and colour of the product packaging [ 23 , 25 , 28 , 32 , 33 , 43 , 61 , 66 , 70 , 71 ]; The ingredients of the product [ 24 , 29 , 39 , 40 , 49 , 57 , 64 , 76 ]; Product category [ 54 , 61 , 69 , 70 , 75 , 78 ]; Organic origin of the product [ 5 , 31 , 42 , 45 , 46 , 48 , 51 , 55 , 68 ]...…”
Section: Resultsmentioning
confidence: 99%
“…When companies provide consumers with information related to nutritional value or to health effects in some way on the product packaging, it has a positive effect on perceived healthiness [ 26 , 34 , 35 , 36 , 47 ]. At the same time, care must be taken that consumers comprehend this information correctly, so that they do not evoke undesired associations [ 62 ], and consumer scepticism related to health claims must also be taken into account [ 74 ], as in this case information may even have a negative effect on assessing healthiness.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported different findings regarding impact of food labels on the consumers' acceptance of FF. Some of them reported positive effects [18,42] and some others released negative ones due to distrust to labels and health claims on the consumption of these products [43,44]. It should be noted that reliable information on the food label is a noteworthy point.…”
Section: Discussionmentioning
confidence: 99%
“…There has been little research specifically into older consumers’ views and use of functional foods (e.g., Vella, Stratton, Sheeshka, & Duncan, ; van der Zanden, van Kleef, de Wijk, & van Trijp, ; Annunziata, Vecchio, & Kraus, ). Furthermore, there has not been research on consumers’ attitudes towards innovative non‐edible products with health effects.…”
Section: Introductionmentioning
confidence: 99%